NATIONAL AND CULTURAL SPECIFICITY OF SUBSTANTIVE PHRASES (Web of Teachers: Inderscience Research, 2026)
This study examines the national and cultural features of substantive word combinations (noun phrases) in a comparative linguistic perspective. Focusing on English and Uzbek, it highlights the influence of cultural values and linguistic traditions on meaning. Findings show that noun phrases serve both grammatical functions and reflect cultural identity and worldview.